Hyaluronic acid-modified curcumin-copper complex nano delivery system for rapid healing of bacterial prostatitis. (15th June 2023) - Gao, Yanyao; Liu, Kailai; Zhang, Yuchen; Sun, Zhenye; Song, Bin; Wang, Yong; Zhang, Bo; Chen, Xi; Hu, Datao; Wen, Jinpeng; Wang, He; Wang, Ke; et al.
Abstract: Bacterial prostatitis is a bacterial infection of the prostate gland presenting with lower quadrant abdominal pain, urination disorders and poor fertility. In recent years, reports have emerged on the significantly reduced efficacy of fluoroquinolone drugs attributed to multiple drug-resistant bacteria, emphasizing the need for new drugs. In this study, we designed a targeting drug delivery system via curcumin copper complex grafted with hyaluronic acid. Subsequently, the prepared system was characterized using FT-IR, XRD, SEM, XPS and 1 H NMR methods. In addition to the substantial improvement in the solubility of the carrier, its antibacterial performance and targeting ability were improved. Interestingly, the grafting of hyaluronic acid endowed the carrier with excellent CD44 receptor targeting function and good water solubility, and the complexation of copper ions greatly enhanced its antibacterial capability, especially the inhibitory effect on E. coli . The anti-prostatitis effect of the drug was evaluated comprehensively by establishing a bacterial prostatitis model infected by E. coli . Assessment of the anti-prostatitis effects in vivo indicated that the Cur-Cu@HA delivery system could effectively promote recovery from bacterial prostatitis by downregulating inflammation. In conclusion, our Cur-Cu@HA delivery system has great potential for treating bacterial prostatitis.